Anodised porous Nb2O5 for photoreduction of Cr(VI). (2019) - Alias, N.; Rosli, S.A.; Hussain, Z.; Kian, T.W.; Matsuda, A.; Lockman, Z.
Abstract: Porous niobium pentoxide (Nb2 O5 ) was successfully formed in a fluorinated sodium sulphuric electrolyte by anodisation process. The anodisation temperature was varied from 25 to 80 °C as to study the effect of anodisation temperature on the morphology of porous Nb2 O5. Porous oxide was formed when the anodisation bath temperature was at 25 o C and 50 o C but not at 80 o C. The anodised niobium (Nb) foils were then annealed to obtain an orthorhombic Nb2 O5 phase. Orthorombic Nb2 O5 is an n-type semiconductor which when illuminated with light of appropriate energy can generate free electrons. These electrons can be used to reduce heavy metal ions like chromium(VI) [Cr(VI)]. Cr(VI) is a typical pollutant often found in industrial wastewater. It is carcinogenic, mutagenic and can induce severe health problem if consumed beyond the limitation. In here, we demonstrated on the possibility of reducing Cr(VI) to a more benign Cr(III) by using free electrons formed upon Nb2 O5 illumination. The photocatalytic reduction of Cr(VI) on porous Nb2 O5 was observed and assessed. The result shows that different anodisation temperature effect on the morphology and pores dispersion; which affect the photoreduction performance. Photoreduction activity was recorded to be ∼ 60 % after 120 min of exposure of the Cr(VI) solution to ultraviolet radiation.